A study to evaluate the significance of Mantoux test investigated for tuberculosis in a tertiary care teaching hospital of India - Saborni Dey; Siddarath Kumar; Vivek Tyagi; Venkata Sai Charan (Asian Journal of Medical Sciences, 2023)
Background: Tuberculosis (TB) is a serious illness that mainly affects the lungs. The Mantoux tuberculin skin test (TST) is one method of determining whether a person is infected with Mycobacterium tuberculosis. Reliable administration and reading of the TST requires standardization of procedures, training, supervision, and practice. Aims and Objectives: The objective was to determine the sensitivity and specificity of Mantoux test in pediatric patients for the diagnosis of TB. It also assists to study various presentations of TB in Mantoux test-positive patients. Materials and Methods: From August 2022 to January 2023, a single tertiary care facility named Saraswathi Institute of Medical Sciences, Hapur hosted this observational study after approval from the Institutional Ethical Committee. Participants in the trial included all children up to 15 years of age who has received Bacillus Calmette-Guérin at birth, were suspected of having TB and had been referred to a pediatric TB clinic. TST by 5 Tuberculin Unit Purified Protein Derivative-Standard was used to see induration of various sizes. The sensitivity, specificity, positive predictive value, negative predictive value and other metrics were calculated during the study by statistical software. Results: Out of 480 patients 36.87% (n=177) had TB with TST cut off≥15 mm indurations, while 169 patients had no induration. Most common age group affected was 5–10 years (48.59%) followed by 0–5 years (30.51%) and 10–15 years (20.90%) with male: female ratio = 1.2:1. Most common etiology for TST positive patients was pulmonary TB (PTB) (29.30%), extra PTB (50.10%), disseminated TB (12.90%) and latent TB (07.70%). The sensitivity of the test was 95.857% with 95% confidence interval (91.64–98.31%), specificity was 95.176% (92.16–97.29%). Its positive and negative predictive values were 91.525% and 97.689% respectively. Conclusion: TB can be diagnosed with the Mantoux test because of its high sensitivity and specificity but it should be explained carefully to avoid inaccurate interpretations.